Die Philosophie der Gegenwart in Selbstdarstellungen. Mit einer Einführung. Hrsg. von R. Schmidt (Meiner)
Mit Bibliogr. und Prtn. 1.Paul Barth, Erich Becher, Hans Driesch, Karl Joël, A. Meinong, Paul Natorp, Johannes Rehmke, Johannes Volkelt. 1923. XX, 224 S.